Genetic variation in alcohol dehydrogenase (ADH1A, ADH1B, ADH1C, ADH7) and aldehyde dehydrogenase (ALDH2), alcohol consumption and gastric cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. - Duell, E; Sala, N; Travier, N; Muñoz, X; Boutron-Ruault, M; Clavel-Chapelon, F; Barricarte, A; Arriola, L; Navarro, C; Sánchez-Cantalejo, E; Quirós, JR; Krogh, V; et al. (2012)
Studies that have examined the association between alcohol consumption and gastric cancer (GC) risk have been inconsistent. We conducted an investigation of 29 genetic variants in alcohol metabolism loci (alcohol dehydrogenase, ADH1 gene cluster: ADH1A, ADH1B and ADH1C; ADH7 and aldehyde dehydrogenase, ALDH2), alcohol intake and GC risk. We analyzed data from a nested case-control study (364 cases and 1272 controls) within the European Prospective Investigation into Cancer and Nutrition cohort. Single nucleotide polymorphisms (SNPs) were genotyped using a customized array. We observed a statistically significant association between a common 3'-flanking SNP near ADH1A (rs1230025) and GC risk [allelic odds ratio (OR)(A v T) = 1.30, 95% confidence interval (CI) = 1.07-1.59]. Two intronic variants, one in ADH1C (rs283411) and one in ALDH2 (rs16941667), also were associated with GC risk (OR(T v C) = 0.59; 95% CI = 0.38-0.91 and OR(T v C) = 1.34; 95% CI = 1.00-1.79, respectively). Individuals carrying variant alleles at both ADH1 (rs1230025) and ALDH2 (rs16941667) were twice as likely to develop GC (OR(A+T) = 2.0; 95% CI = 1.25-3.20) as those not carrying variant alleles. The association between rs1230025 and GC was modified by alcohol intake (<5 g/day: OR(A) = 0.89, 95% CI = 0.57-1.39; ≥5 g/day: OR(A) = 1.45, 95% CI = 1.08-1.94, P-value = 0.05). The association was also modified by ethanol intake from beer. A known functional SNP in ADH1B (rs1229984) was associated with alcohol intake (P-value = 0.04) but not GC risk. Variants in ADH7 were not associated with alcohol intake or GC risk. In conclusion, genetic variants at ADH1 and ALDH2 loci may influence GC risk, and alcohol intake may further modify the effect of ADH1 rs1230025. Additional population-based studies are needed to confirm our results.